2020
DOI: 10.1111/jgh.15102
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review on the definition and predictors of severe Clostridiodes difficile infection

Abstract: Clostridiodes difficile infection (CDI) is one of the most common hospital‐acquired infections with high mortality rates. Optimal management of CDI depends on early recognition of severity. However, currently, there is no acceptable standard of prediction. We reviewed severe CDI predictors in published literature and its definition according to clinical guidelines. We systematically reviewed studies describing clinical predictors for severe CDI in medical databases (Cochrane, EMBASE, Global Health Library, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 59 publications
(94 reference statements)
3
11
0
Order By: Relevance
“…Our findings are in line with two recently published systematic reviews on predictors of sCDI that reported age and presence of comorbidities as the two most important severity predictors for CDI (162,165). Similarly, previous reviews on prognostic factors for rCDI found that older age, prior CDI and PPI therapy were risk factors for rCDI (162)(163)(164)(165). However, PPI therapy in general did not show a clear association in our study.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our findings are in line with two recently published systematic reviews on predictors of sCDI that reported age and presence of comorbidities as the two most important severity predictors for CDI (162,165). Similarly, previous reviews on prognostic factors for rCDI found that older age, prior CDI and PPI therapy were risk factors for rCDI (162)(163)(164)(165). However, PPI therapy in general did not show a clear association in our study.…”
Section: Discussionsupporting
confidence: 91%
“…Our systematic review on prognostic factors resulted in several expected and unexpected findings when compared with previous reviews rCDI (162)(163)(164). Our findings are in line with two recently published systematic reviews on predictors of sCDI that reported age and presence of comorbidities as the two most important severity predictors for CDI (162,165). Similarly, previous reviews on prognostic factors for rCDI found that older age, prior CDI and PPI therapy were risk factors for rCDI (162)(163)(164)(165).…”
Section: Discussionsupporting
confidence: 88%
“…The finding of serum albumin being a predictor of mortality is concordant with our previous systematic review, which showed that at least five of the 31 articles identified prior comorbidities, age, white blood cell count, serum albumin, serum creatinine and ICU admission as predictors of severity. 14 Interestingly, none of the 31 studies on C. difficile severity predictors included lactate and bicarbonate levels. Furthermore, all international clinical guidelines on severe CDI, such as American College of Gastroenterology and European Society of Clinical Microbiology and Infectious Diseases, do not include lactate and bicarbonate levels.…”
Section: Discussionmentioning
confidence: 99%
“… 13 We recently published a systematic review of severe CDI predictors, but found that present risk scoring systems have been limited by small sample size and heterogeneity in definition of severe CDI. 14 Proposed severity scores such as Clostridiodes difficile Associated Risk of Death Score (CARDS) 15 and ATLAS Score 16 17 (combination of age, treatment with systemic antibiotics, leucocyte count, serum albumin and serum creatinine) have not been widely adopted in current clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…Among all the teams in healthcare datathon over the years, we found that on average, 10% of teams remained active after the event. They were able to formalize their clinical problems into research projects and produce impactful publications (16)(17)(18)(19). For example, van den Boom et al (16) were a group of researchers who participated in healthcare datathon 2018 in Singapore and formed a research team to study the optimal oxygen saturation target for critically ill patients.…”
Section: Discussionmentioning
confidence: 99%